Safety aspects of cluster immunotherapy with semi-depot allergen extracts in seasonal allergic rhinoconjunctivitis - Pfaar, Oliver; Mösges, Ralph; Hörmann, Karl; Klimek, Ludger (European archives of oto-rhino-laryngology and head & neck, 2010)
In addition to allergen avoidance and pharmaceutical medication, specific immunotherapy (SIT) stands for the third most important mainstay offered to allergic patients. SIT has been widely used in pollen-allergic rhinitis, and clinical efficacy has been validated in several controlled clinical trials. Classic SIT protocols begin with an initial dose-increase period (subcutaneous injections of gradually ascending dosages of the allergen extract in weekly intervals) followed by the dose-maintenance period. However, dosage schedules are not commonly standardized yet. Cluster-SIT is an accelerated procedure to achieve the maintenance dose after a shorter time interval by the application of 2-3 injections per treatment day. A total of 395 pollen-allergic patients (173 females, 222 males) aging from 18 to 61 years (mean age 32.6 ± 5.9 years) have been investigated using a Cluster schedule for Alutard SQ that allows updosing up to 100,000 SQ-U in six treatment days (within 5 weeks). The schedule was investigated with regard to the side effects during dosage increase. The total number of systemic reactions was n = 148 or 2.05% of all injections. Of these, 119 (80%) were classified as immediate reactions, 27 (18%) were late-phase reactions and 2 (2%) were both immediate- and late-phase reactions. Of all systemic reactions, 124 (84%) were classified as grade 1 reactions, and 24 (16%) as grade 2. No reactions of grades 3 and 4 occurred. Age, gender and the type of the allergen used had no influence on the frequency or severity of local or systemic reactions. The appearance and amount of adverse side effects in Cluster-SCIT is comparable to those in conventional schedules. With respect to safety aspects, this accelerated dosage schedule could turn into an interesting alternative for dosage increase during subcutaneous immunotherapy (SCIT).
Online veröffentlicht: 16. September 2009
Gesehen am 28.04.2023